Failure assessment of the shaft of a pumped storage unit. (28th March 2014) - Negru, R.; Muntean, S.; Pasca, N.; Marsavina, L.; Pantelakis, Spiros; Berto, Filippo; Lazzarin, Paolo
ABSTRACT The paper is focused on failure assessment of the shaft of a pumped storage unit. The shaft failure occurred during normal operation of the hydropower unit after 35 years of service. Three different methods are applied in order to assess its lifetime. Firstly, a finite element analysis was performed in order to obtain the static stress distribution and to apply a strain‐based crack initiation for the shaft under torsion load. The number of cycles for crack propagation was obtained using the Paris law for mode III. More precisely, the lifetime assessment of the shaft is obtained based on a low‐cycle fatigue analysis for estimating the number of cycles for crack initiation and then followed by that for fatigue crack propagation. Secondly, an analytical estimation based on failure assessment diagram is carried out for circumferential crack in order to determine the safe/unsafe region, where the shaft can operate with a crack. The failure assessment diagram for mode III loading was plotted in order to obtain the critical circumferential crack using the stress intensity factor solution and three analytical solutions for plastic zone. Thirdly, the theory of critical distance is employed for estimating the shaft life under torsional loading. A good agreement is obtained between the estimated results and experimental data for the shaft life and the crack length.